2016
DOI: 10.1053/j.jvca.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Off-Pump Bilateral Cadaveric Lung Transplantation Is Associated With Profound Intraoperative Hypothermia

Abstract: Patients undergoing off-pump BLT were at high risk of profound intraoperative hypothermia despite multimodal preventive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…One study showed that patients undergoing off-pump BLT were at higher risk of profound intraoperative hypothermia despite multimodal preventive therapy. Off-pump SLT had a similar time trend for their body temperature but the extent of the decrease was much smaller than that in off-pump BLT patients 33 …”
Section: Discussionmentioning
confidence: 85%
“…One study showed that patients undergoing off-pump BLT were at higher risk of profound intraoperative hypothermia despite multimodal preventive therapy. Off-pump SLT had a similar time trend for their body temperature but the extent of the decrease was much smaller than that in off-pump BLT patients 33 …”
Section: Discussionmentioning
confidence: 85%
“…Often, surgical technique and cardiac manipulation may lead to major challenges such as hemodynamic instability and cardiovascular collapse. 8 Although this strategy avoids anticoagulation, decreases intraoperative transfusion, and decreases mechanical circulatory support-induced inflammatory response, 9 the off-pump strategy does not allow for controlled graft reperfusion. The overall utilization of the off-pump technique remains controversial and has its own separate considerations and risks, which are beyond the scope of this discussion on perioperative ECLS management.…”
Section: Discussionmentioning
confidence: 99%